PTEN in somatostatin neurons regulates fear and anxiety and is required for inhibitory synaptic connectivity within central amygdala - Holford, Timothy W.; Letourneau, Kaitlyn N.; Von-Walter, Carolyn; Moncaleano, Daniela; Loomis, Cody L.; Bolton, M. McLean (Frontiers in Cellular Neuroscience, 2025)
IntroductionThe phosphatase and tensin homolog deleted on chromosome 10 (PTEN) is a negative regulator of the mTOR pathway and is strongly associated with autism spectrum disorder (ASD), with up to 25% of ASD patients with macrocephaly harboring PTEN mutations. Mice with germline PTEN haploinsufficiency show behavioral characteristics resembling ASD, as do various mouse models with conditional knockouts of PTEN. Human tissue studies and those from multiple genetic mouse models suggest that dysfunction of GABAergic interneurons may play a role in the development of ASD, but the precise mechanisms remain elusive. PTEN provides a target for investigation because it regulates the development of inhibitory neurons arising from the medial ganglionic eminence, promoting the survival and maturation of parvalbumin (PV+) neurons at the expense of somatostatin (SOM+) neurons.MethodsHere, we investigate how PTEN regulates SOM+ neurons at the cellular and circuit level in the central lateral amygdala (CeL), an area that governs the key ASD behavioral symptoms of social anxiety and altered emotional motivation for social engagement using behavioral analysis, electrophysiology, and two-photon local circuit mapping.ResultsWe found that knocking out PTEN in SOM+ neurons results in elevated levels of fear and anxiety and decreases CeL local circuit connectivity. Specifically, this manipulation decreased the strength of connections between individual neurons and altered the distribution of local connections in a cell-type specific manner. In contrast to the deficit in local inhibitory connections within CeL, the excitatory drive from the major CeL input, the basolateral amygdala (BLA) was enhanced.DiscussionThis combined imbalance of enhanced excitation and diminished local inhibition likely underlies the heightened fear learning and anxiety we observed in the PTEN-SOM-KO mice.